Social Preferences for Orphan Drugs: A Discrete Choice Experiment Among the French General Population - Toumi, Mondher; Millier, Aurélie; Cristeau, Olivier; Thokagevistk-Desroziers, Katia; Dorey, Julie; Aballéa, Samuel (Frontiers in Medicine, 2020)
Objectives: While several authors have suggested using a multi-criteria approach for orphan drug assessment and proposed lists of determinants of orphan drug value, studies on social preferences regarding these determinants remain limited. The current study aimed to identify preferences of the French general population regarding attributes characterizing the value of orphan drugs in a discrete choice experiment. Methods: The list of attributes was formed based on a literature search and was refined through expert interviews, a focus group, and a pilot study. The final list included nine attributes: disease-associated disability, disease-associated mortality, number of patients, availability of alternative treatments, treatment impact on disease disability, treatment impact on mortality, treatment safety, uncertainty around therapeutic effect, and annual treatment cost per patient. Members of the General Public were presented with 12 choice sets containing two drug profiles described according to the attributes and an option to fund neither of these treatments. The questionnaire was disseminated online. A conditional logit model with random effects was used to estimate the weight of each attribute. Results: A total of 958 persons participated in the study (48.7% male, mean age: 47.5 years). All attributes except for disease-associated disability had a statistically significant influence on the choices made by participants. The attribute with the highest weight was treatment impact on mortality (p<0.0001), followed by uncertainty around therapeutic effect (p<0.0001). The direction of results was generally consistent with intuition: patients preferred a drug with a larger impact on mortality, a larger impact on disability, with mild or no adverse events, with less uncertainty. Although patients appeared to prefer drugs with a lower budget impact, the relationship between patient preferences and costs was more complex. Conclusions: Preferences of the general public between orphan drugs are mostly driven by the impact on mortality and the degree of certainty regarding the available evidence.